2020
DOI: 10.31703/ger.2020(v-i).18
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Economic Correlates of Children's Nutritional Status: Evidence from Pakistan Demographic and Health Survey 2017-18

Abstract: Nutrition status is an important indicator of child health. This study estimates the effect of socioeconomic determinants on children's nutritional status of under five years of age. We apply the Composite Index of Anthropometric Failure (CIAF) in our empirical analysis as a proxy measure to denote the malnutrition measurement index, and a binary logistic regression model using PDHS dataset for 2017-18. The logistic regression model inspects the probability of malnutrition among children. The result demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
(21 reference statements)
3
2
0
Order By: Relevance
“…It portrayed that with an increase in age, the prevalence of malnutrition also increased. The results were consistent with the previous literature [ 44 , 45 , 46 ]. The consequences of the study were that the chances of malnutrition were higher in children belonging to the Sindh, Balochistan, and KPK regions/provinces.…”
Section: Discussionsupporting
confidence: 94%
“…It portrayed that with an increase in age, the prevalence of malnutrition also increased. The results were consistent with the previous literature [ 44 , 45 , 46 ]. The consequences of the study were that the chances of malnutrition were higher in children belonging to the Sindh, Balochistan, and KPK regions/provinces.…”
Section: Discussionsupporting
confidence: 94%
“…Children in the age group 25-48 months have a greater chance of being undernourished in comparison with other age groups. These results are aligned with some previous studies in Pakistan [36][37][38][39]. Additionally, household income decreases the probability of malnutrition in children.…”
Section: Discussionsupporting
confidence: 92%
“…The study findings depicted that educated mothers have less likelihood of malnourishment prevalence among their children under the age of five. Certain past investigations also supported our findings that the education of females is a significant cause of malnutrition [ 42 , 43 , 44 , 45 , 46 ]. Another study from Sindh Province also identified maternal illiteracy, overcrowding, and low income as significant stunting risk factors [ 47 ].…”
Section: Discussionsupporting
confidence: 90%